Urbanization and Its Impact on Land Use and Land Cover in Dhangadi Sub-Metropolitan City: Comprehensive Analysis and Forecasting - Paudel, Indra Raj; Bhurtyal, Umesh; Lamichhane, Sadhuram; Pokharel, Bimal; Katuwal, Netra Bahadur (Journal of Engineering and Sciences, 2024)
Urbanization, a global phenomenon characterized by the growth and expansion of urban areas, presents significant challenges and opportunities for sustainable development. This study investigates the spatial impact of urbanization on land use and land cover (LULC) in Dhangadhi Sub-metropolitan City (DSMC) from 2002 to 2022 and forecasts urban sprawl for 2032 using CA-Markov chain analysis. The CA-Markov model simulates future land use changes based on historical data. Landsat images from 2002, 2012, and 2022 were analyzed using the Maximum Likelihood algorithm, classifying the landscape into agricultural land, barren land, forest land, built-up area, and water bodies. Weighted overlay and suitability analyses considered physical, accessibility, social, economic, and environmental factors to create a suitability map for future urban development. The LULC analysis showed significant changes: agricultural land decreased from 58.35% in 2002 to 26.31% in 2022, while the built-up area expanded from 6.03% to 33.48%. Accuracy assessments confirmed the reliability of the classification results, with high user and producer accuracies and kappa values. The results indicated significant urban expansion into peri-urban and rural areas, driven by population growth, economic activities, and inadequate urban planning. Ecological consequences include biodiversity loss, habitat fragmentation, and climate changes, while social impacts involve community structure and service access, and economic impacts affect land value and infrastructure costs. The forecast for 2032 suggests continued urban expansion, emphasizing the need for sustainable urban planning. Recommended strategies include green belt development, zoning regulations, promoting public transportation, protecting agricultural land, preserving natural habitats, and involving local communities in planning. These findings offer valuable insights for policymakers and urban planners in DSMC to manage growth sustainably and mitigate the adverse effects of urban sprawl.